Implementation of Islamic Corporate Governance Principles in Sharia Financial Services Institutions Amid Digital Transformation to Strengthen Consumer Protection and Business Ethics - Ahmad Fadilah Ilmi Nasution (Journal of International Islamic Business Studies, 2025)
This study analyzes the implementation of Islamic Corporate Governance principles in Islamic financial services institutions in the midst of digital transformation to strengthen consumer protection and Islamic business ethics through a descriptive qualitative approach based on literature studies from scientific books, national-international journals, and financial authority websites; Data analysis includes reduction, narrative presentation, and conclusion drawing to illustrate the gap between sharia norms and operational practices. The results show that the implementation of the principles of accountability, transparency, fairness, and trust via DPS as well as technologies such as blockchain and AI on sharia fintech platforms has succeeded in increasing the efficiency of mudharabah transactions and automatic zakat distribution, but is hampered by low DPS literacy, immature cybersecurity regulations, outdated legacy infrastructure, minimal consumer literacy, and minimal stakeholder collaboration which triggers the risk of data leakage, hidden ghara, and business ethics shifted to commercial orientation; The role of Islamic Corporate Governance has proven to be essential to strengthen real-time supervision, sharia grievance redressal, and digital Islamicity index to maintain halal integrity and falah in the midst of innovations such as robo-advisory and tokenized sukuk.